Moment-Based Distributionally Robust Peer-to-Peer Transactive Energy Trading Framework Between Networked Microgrids, Smart Parking Lots and Electricity Distribution Network - Nasiri, Nima; Zeynali, Saeed; Najafi Ravadanegh, Sajad; Kubler, Sylvain (IEEE transactions on smart grid, 2024)
This paper proposes a decentralized scheduling framework for peer-to-peer (P2P) transactive energy trading between prosumers and the local electricity market (LEM). In this approach, prosumers are modeled in the form of networked microgrids (NMG) and smart parking lots (SPL), which can exchange energy in a P2P framework. At the same time, each of the prosumers exchanges information and energy with the LEM in a decentralized approach based on the distribution locational marginal price (DLMP). The LEM is modeled by an active radial electricity distribution network (EDN), considering a high penetration of renewable energy sources (RES) and the feeder power losses in a convex optimization model. In proposed P2P transactive energy model, the alternating direction method of multipliers (ADMM) has been used to achieve the equilibrium point between peers. The distributionally robust optimization (DRO) method has been used to model the uncertain behavior of RES in NMGs, SPLs, and the EDN. In addition, the impact of applying smart charging strategies for electric vehicles (EV) in the proposed P2P transactive energy model has been investigated. To confirm the functionality of the model, 12-bus, 6-bus, and 4-bus networks have been used to model NMGs, while the EDN is embodied by a standard IEEE 33-bus and 123-bus test systems.